Influenza vaccination type, live, attenuated influenza vaccine (LAIV) versus inactivated influenza vaccine (IIV), received by children, United States, 2011-12 through 2013-14 influenza seasons - Kahn, Katherine E. (Vaccine, 2015)
BACKGROUND: Influenza vaccines available for children in the United States include inactivated influenza vaccine (IIV) and live, attenuated influenza vaccine (LAIV). Objectives of this study were to quantify proportions of IIV and LAIV received by vaccinated children, and examine associations between vaccine type received and demographic characteristics. METHODS: National Immunization Survey-Flu (NIS-Flu) parental reported data for the 2011-12 through 2013-14 influenza seasons were used to estimate proportions of vaccinated children 2-17 years who received IIV and LAIV. Tests of association between vaccination type and demographic variables were conducted using Wald chi-square tests and pair-wise comparison t-tests. Multivariable logistic regression was used to determine variables independently associated with receipt of LAIV versus IIV. RESULTS: In the 2013-14 season, 33.3% of vaccinated children received LAIV, similar to the proportion in the 2011-12 (32.2%) and 2012-13 (32.1%) seasons. Across all seasons studied, the strongest observed association was between vaccination type and child's age, with children 2-8 years (Adjusted Prevalence Ratio (95% confidence interval) [APR(95% CI)] 1.41(1.27-1.56), 1.46(1.34-1.59), and 1.50(1.38-1.63) for 2011-12, 2012-13, and 2013-14) and 9-12 years (APR(95% CI) 1.37(1.23-1.54), 1.38(1.26-1.51), and 1.50(1.38-1.63) for 2011-12, 2012-13, and 2013-14) being more likely to have received LAIV than children 13-17 years. Among those vaccinated, whites were more likely to have received LAIV compared to blacks (APR(95% CI) 1.19(1.05-1.35), 1.24(1.10-1.39), and 1.22(1.11-1.34) for 2011-12, 2012-13, and 2013-14), and children living above poverty (annual income >$75,000) were more likely to have received LAIV than those living at or below poverty (APR(95% CI) 1.43(1.23-1.67), 1.13(1.02-1.26), and 1.16(1.06-1.28) for 2011-12, 2012-13, and 2013-14). CONCLUSIONS: This study provides a baseline of the extent and patterns of LAIV uptake that can be used to measure the impact of relevant public health policy. Additional research is needed to investigate parental and provider preferences and barriers regarding LAIV.